Glutaminase isoenzymes in the metabolic 1 therapy of cancer - Mates-Sánchez, José Manuel; Campos-Sandoval, José Ángel; Márquez-Gómez, Javier (Elsevier, 2018)
Altered cellular metabolism is a hallmark of cancer. Cancer cells express isoforms of metabolic enzymes that may constitute therapeutic targets. Glutaminase controls glutamine metabolism and their expression correlate with malignancy of tumours. The two types of glutaminase isoenzymes, GLS and GLS2, differ in their expression patterns and functional roles: GLS has oncogenic properties and GLS2 has been described as a tumour suppressor factor. Selective genomic and epigenomic intervention over glutaminase affects the metabolic reprogramming of cancer. This review highlights the molecular metabolic vulnerabilities in various types of cancer, to be used for biomarker development, drug design, and in personalized oncology.
Mensaje de la editorial Elsevier: Dear Dr. José A. Campos-Sandoval, I have attached the accepted version of your manuscript for your reference. Kindly check and let me know if you need any further assistance. Best regards, Narmatha Journal Manager
Keywords: Cáncer - Aspectos moleculares; Antiangiogénicos; Cancer metabolism; Combinatory therapy; Glutaminase inhibitors; Glutamine; Glutaminase isoenzymes; Metabolic reprogramming